2004
DOI: 10.1016/j.jasms.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of protonated ions of peptides containing cysteine, cysteine sulfinic acid, and cysteine sulfonic acid

Abstract: The oxidation of the sulfhydryl group in cysteine to sulfenic acid, sulfinic acid, and sulfonic acid in proteins is important in a number of enzymatic processes. In this study we examined the fragmentation of four peptides containing cysteine, cysteine sulfinic acid (Cys-SO 2 H), and cysteine sulfonic acid (Cys-SO 3 H) in an ion-trap mass spectrometer. Our results show that the presence of a Cys-SO 2 H in a peptide leads to preferential cleavage of the amide bond at the C-terminal side of the oxidized cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 25 publications
8
32
0
3
Order By: Relevance
“…34,–38 Our findings are also consistent with previous CID work demonstrating that, under mobile-proton conditions, S -sulfonylation has little influence on critical energies. 48 By contrast, it has been reported that this modification can enhance fragmentation under charge-remote conditions for both ESI and fast atom bombardment-generated peptide ions. 48,49 However, we focus on multiply charged standard peptides with one or less arginines, and on tryptic peptide ions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…34,–38 Our findings are also consistent with previous CID work demonstrating that, under mobile-proton conditions, S -sulfonylation has little influence on critical energies. 48 By contrast, it has been reported that this modification can enhance fragmentation under charge-remote conditions for both ESI and fast atom bombardment-generated peptide ions. 48,49 However, we focus on multiply charged standard peptides with one or less arginines, and on tryptic peptide ions.…”
Section: Resultsmentioning
confidence: 95%
“…48 By contrast, it has been reported that this modification can enhance fragmentation under charge-remote conditions for both ESI and fast atom bombardment-generated peptide ions. 48,49 However, we focus on multiply charged standard peptides with one or less arginines, and on tryptic peptide ions.…”
Section: Resultsmentioning
confidence: 95%
“…In each case, the active-site thiol was the most susceptible to HOSCN-induced sulfenic acid formation, with oxidation of other thiol residues on CK and GAPDH observed at higher oxidant concentrations. The MS/MS fragmentation patterns of Cys–SO 2 H-containing peptides are characteristically dominated by fragments corresponding to cleavage of the peptide C-terminal to the Cys–SO 2 H, in addition to an increased abundance of fragment ions originating from neutral losses of H 2 O and H 2 SO 2 , from the precursor and b n fragment ions [54,55]. For CK, the fragmentation spectra of the Cys-282 + 32 peptide is dominated by fragments corresponding to C-terminal Cys–SO 2 H cleavage ( b 17 ) and neutral losses (H 2 O, H 2 SO 2 ) from the [M + 2H] 2+ species.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide was oxidized using Fenton reagents (Fe +2 /H 2 O 2 ) as reported previously [36]. Briefly, 1 mM peptide solution was incubated at room temperature in the presence of 0.5 mM FeSO 4 and 0.2 mM H 2 O 2 for approximately 30 min.…”
Section: Methodsmentioning
confidence: 99%